Implications of Slow Atmospheric Chromium Oxidation for the Disposal of Smelter Slags and Finishing Plant Sludges - Harro von Blottnitz; Jochen Petersen (International Mineral Processing Congress, 2003)
"The landfill disposal of slags is common practice in the metallurgical industry. Chromium may be a minor constituent in many cases. It is present mostly in the form of chromites, which are considered environmentally benign and hence safe for disposal. Wastewaters from metal finishing operations are most commonly treated by reduction and precipitation of dissolved metals, including chromium, by lime addition, and subsequent landfill disposal of the resulting sludge. The metals contained in such sludges are mostly in the form of hydroxides, and as such considered environmentally stable.Thermodynamically, trivalent chromium, which is the predominant form in these waste materials, can be oxidised to the hexavalent form by atmospheric oxygen. Detailed research work on both slags and sludges has shown that a gradual emergence of hexavalent chromium can indeed be observed. The mechanism is governed by close physical contact between chromium oxide (or hydroxide) phases on the one side and calcium oxide (or hydroxide), which is present as flux in slags and residual lime in sludges, on the other. If oxygen can migrate to the points of contact, gradual formation of calcium chromate ensues.Hexavalent chromium is associated with high environmental toxicity, and hence undesirable in landfilled materials. Moisture migrating through landfill deposits can mobilise the highly soluble chromates and thus potentially transport them into natural waterways. Such gradual release from stainless steel and ferrochromium slag deposits has been demonstrated in a column experiment."